Successful treatment of pulmonary lymphatic perfusion syndrome with lymphatic intervention embolization: a case report - Liu, Qunxiang; Wang, JiaQi; Chen, Yingjie; Qin, Wei; Zhu, Ziyang (Frontiers in Medicine, 2025)
Pulmonary Lymphatic Perfusion Syndrome (PLPS) is a rare condition characterized by abnormal lymphatic drainage into the lungs, leading to symptoms such as chyloptysis and chylous effusions. We report a case of a 54-year-old male with PLPS who presented with persistent cough, milky sputum, and pericardial effusion. Following initial misdiagnosis and ineffective empirical treatment for a presumed pulmonary infection, a definitive diagnosis of PLPS was established. The patient underwent successful percutaneous thoracic duct embolization, resulting in complete resolution of symptoms and imaging findings at follow-up. This case highlights the importance of considering PLPS in patients with unexplained chylous effusions and the efficacy of lymphatic intervention as a treatment option.